Two new species of Pyrgulopsis Call & Pilsbry, 1886 (Mollusca: Caenogastropoda: Hydrobiidae) from springs in the Rio Grande watershed in Texas - Perez, Kathryn E.; Leal, Manuel Spor; Glover, Houston; Chastain, Rebecca T.; Hutchins, Benjamin T.; Schwartz, Benjamin (Zootaxa, 2021)
Pyrgulopsis Call & Pilsbry, 1886 is a genus of small (<5 mm) spring snails, usually endemic to single freshwater springs. Two new populations of Pyrgulopsis found in very small, isolated springs and spring runs in the mainstem Rio Grande watershed of western Texas are distinguished from congeners. Mitochondrial and nuclear sequences, morphometrics, and morphological characteristics support Pyrgulopsis rubra sp. nov. and Pyrgulopsis harrymilleri sp. nov. as distinct from other known Pyrgulopsis species, including the geographically proximate P. metcalfi.